Managing Allergic Nickel Dermatitis in Occupational Settings: A Case Report - Mendes Ribeiro, Rui André; Teófilo, Vanessa; Moreira, Salomé; Pinho, Paulo; Norton, Pedro; Pereira, Teresa (La Medicina del Lavoro, 2024)
Contact dermatitis is a common cutaneous inflammatory condition, triggered by exposure to irritant substances or allergens. Nickel is the most prevalent allergen, a metal widely used in accessories, furniture, office materials, food and in industry, with multiple exposure pathways, making it difficult to assess which exposure is causing allergic dermatitis. Here, we report a case of an administrative worker with chronic hand eczema, limited to the radial metacarpophalangeal region of the left hand, caused by occupational exposure to nickel, confirmed by nickel deposition test on the hand and a positive test with a metallic stapler used at her workplace.